Rehabilitation professionals' views on social media use in traumatic brain injury rehabilitation: gatekeepers to participation. Issue 14 (3rd July 2021) - Brunner, Melissa; Togher, Leanne; Palmer, Stuart; Dann, Stephen; Hemsley, Bronwyn
Abstract: Purpose: Rehabilitation professionals support people with traumatic brain injury (TBI) to return to meaningful participation in life and society – which now includes the use of social media. However, the role of health professionals in supporting the use of social media by adults with TBI is not yet known. This study aimed to investigate the experiences and views of rehabilitation professionals on the use of social media by people with TBI during rehabilitation. Method: Two focus groups were conducted and analysed qualitatively for content themes. Results: Eleven rehabilitation professionals, including allied health, recreational therapy, and service management, took part in this study. Participants identified potential benefits to people with TBI using social media, including reduced social isolation. However, they expressed concerns about social media risks relating to the vulnerability, exploitation, and reputation management for people with TBI. Rehabilitation professionals viewed their role as being to protect people from these risks of harm, either through imposing restrictions on social media use or responding to problems after these occurred. Conclusion: A knowledge translation approach might help guide and support rehabilitation professionals in enabling adults with TBI to safely access and experience the benefits of meaningful engagement in social media during rehabilitation. Implications for rehabilitation: Rehabilitation professionals can start addressing social media use during collaborative goal setting, in order to support people with traumatic brain injury to use social media successfully during rehabilitation and beyond. To do this, professionals can inquire as to the person's previous social media use and identify priority areas for the person for short- and long-term goals. Rehabilitation targeting social media use should include instruction for participation in social media platforms, providing education and feedback that is positive and constructive, as well as risk management education. Policy and guidance is needed for rehabilitation professionals to more actively support people with traumatic brain injury to access social media for improved participation and inclusion in online communities. Addressing social media goals in rehabilitation should be informed by existing successful traumatic brain injury rehabilitation approaches (e.g., functional rehabilitation) and adopting strategies used in rehabilitation supporting other higher risk goals (e.g., return to driving).